A generalized weighted total least squares-based, iterative solution to the estimation of 3D similarity transformation parameters - Wang, Yongbo; Yuan, Kun; Zheng, Nanshan; Bian, Zhengfu; Yang, Min (Measurement : journal of the International Measurement Confederation, 2025)
Recently, we received a comment from a reader. From the reader’s perspective, he/she shared his/her views on the points discussed in the article, pointing out certain issues. In response to the concerns raised by the reader, we provided detailed answers to each of their questions, along with the source code for the algorithm presented in the article, as well as the source code for the comparison algorithms, to address the reader’s concerns.